2024
DOI: 10.1111/apt.17906
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐induced liver injury from selective androgen receptor modulators, anabolic‐androgenic steroids and bodybuilding supplements in Australia

Emily Nash,
Amanda Nicoll,
Nicholas Batt
et al.

Abstract: SummaryBackgroundReports of DILI due to herbal and dietary supplements have been increasing over time.AimsTo characterise clinical, laboratory and histopathological phenotypes and outcomes of drug‐induced liver injury (DILI) due to anabolic‐androgenic steroids (AAS), selective androgen receptor modulators (SARMs), and bodybuilding supplements (BBS) in Australia.MethodsRetrospective case series. Patients presented to nine Australian tertiary hospitals, 2017–2023. DILI was defined biochemically and patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…3,4 Neither AASs nor SARMs are approved for non-medical use in most countries, but can be purchased illicitly over the Internet. Such products can be adulterated with unlisted compounds and constitute an even higher risk for users, as highlighted by Nash et al 2 Similarly, a chemical analysis of 21 BBSs attributed to DILI in the United States found that 17 of these contained anabolic steroids not listed on the labels.…”
Section: N V I T E D E D I T O R I a L Editorial: Muscles At The Expe...mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Neither AASs nor SARMs are approved for non-medical use in most countries, but can be purchased illicitly over the Internet. Such products can be adulterated with unlisted compounds and constitute an even higher risk for users, as highlighted by Nash et al 2 Similarly, a chemical analysis of 21 BBSs attributed to DILI in the United States found that 17 of these contained anabolic steroids not listed on the labels.…”
Section: N V I T E D E D I T O R I a L Editorial: Muscles At The Expe...mentioning
confidence: 99%
“…Nash et al presented a retrospective case series of 23 DILI cases attributed to AASs, SARMs and/or additional bodybuilding supplements (BBSs), based on information from nine Australian tertiary hospitals over 7 years. 2 The nine cases involving SARMs currently constitute the largest reported case series of SARM hepatotoxicity. Comparing patient characteristics between AASand SARM-induced liver injury, the authors found many similarities.…”
Section: N V I T E D E D I T O R I a L Editorial: Muscles At The Expe...mentioning
confidence: 99%